A variant of LEAFY reveals its capacity to stimulate meristem development by inducing RAX1. (22nd April 2013) - Chahtane, Hicham; Vachon, Gilles; Le, Marie; Thévenon, Emmanuel; Périgon, Sophie; Mihajlovic, Nela; Kalinina, Anna; Michard, Robin; Moyroud, Edwige; Monniaux, Marie; Sayou, Camille; Grbic, Vojislava; et al.
Summary In indeterminate inflorescences, floral meristems develop on the flanks of the shoot apical meristem, at positions determined by auxin maxima. The floral identity of these meristems is conferred by a handful of genes called floral meristem identity genes, among which the LEAFY (LFY) transcription factor plays a prominent role. However, the molecular mechanism controlling the early emergence of floral meristems remains unknown. A body of evidence indicates that LFY may contribute to this developmental shift, but a direct effect of LFY on meristem emergence has not been demonstrated. We have generated a LFY allele with reduced floral function and revealed its ability to stimulate axillary meristem growth. This role is barely detectable in the lfy single mutant but becomes obvious in several double mutant backgrounds and plants ectopically expressing LFY. We show that this role requires the ability of LFY to bind DNA, and is mediated by direct induction of REGULATOR OF AXILLARY MERISTEMS1 (RAX1) by LFY. We propose that this function unifies the diverse roles described for LFY in multiple angiosperm species, ranging from monocot inflorescence identity to legume leaf development, and that it probably pre‐dates the origin of angiosperms.